2022
DOI: 10.3389/fvets.2022.778934
|View full text |Cite
|
Sign up to set email alerts
|

Using Gene Expression Analysis to Understand Complex Autoimmune Skin Disease Patients: A Series of Four Canine Cutaneous Lupus Erythematosus Cases

Abstract: Cutaneous Lupus Erythematosus (CLE) is an autoimmune skin disease that occurs in almost two-thirds of people with Systemic Lupus Erythematosus (SLE) and can exist as its own entity. Despite its negative impact on the quality of life of patients, lupus pathogenesis is not fully understood. In recent years, the role of gene expression analysis has become important in understanding cellular functions and disease causation within and across species. Interestingly, dogs also develop CLE, providing a spontaneous ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In chronic DLE, inflammatory proteins have been identified as a primary cause of the disease. Recent studies suggest that the skin lesion transcriptomes of both canine and human CLEs are similar, with both showing activation of the innate immune system, interferon and JAK (Janus Kinase)‐STAT (Amudzi et al., 2022 ; Harvey et al., 2023 ). An experimental study has shown excellent responses in the treatment of FDLE cases, with improvement observed within the first 2 weeks of using oclacitinib at 1.8 mg/kg twice daily.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic DLE, inflammatory proteins have been identified as a primary cause of the disease. Recent studies suggest that the skin lesion transcriptomes of both canine and human CLEs are similar, with both showing activation of the innate immune system, interferon and JAK (Janus Kinase)‐STAT (Amudzi et al., 2022 ; Harvey et al., 2023 ). An experimental study has shown excellent responses in the treatment of FDLE cases, with improvement observed within the first 2 weeks of using oclacitinib at 1.8 mg/kg twice daily.…”
Section: Discussionmentioning
confidence: 99%
“…6 While infiltrating lymphocytes were identified as the main source of CXCL10 in dogs with associated systemic signs, keratinocytes were the main source in dogs without systemic signs. 6…”
Section: Diagnostic Histological Featuresmentioning
confidence: 99%
“…Targeted transcriptomic analysis of skin lesions from 4 dogs with CLE demonstrated upregulation of IFNG and interferon-related chemokine CXCL10. 6 While infiltrating lymphocytes were identified as the main source of CXCL10 in dogs with associated systemic signs, keratinocytes were the main source in dogs without systemic signs. 6 In general, B lymphocytes are not major players in cytotoxic dermatitis.…”
Section: Cellular Infiltrates Associated With Cytotoxic Dermatitismentioning
confidence: 99%
See 2 more Smart Citations